CARRIER’S OF GOODS NEGLIGENCE AS A CONDITION OF UNLIMITED LIABILITY - Mitkevičius, Vilius (Teisė, 2017)
Author analyses carrier’s limited liability in the context of Republic of Lithuania and international legal regulation of carriage of goods and conception of different types of negligence as a condition for carrier`s unlimited liability.